Further evidence regarding the effect of KAMs on audit report lag - Ayşegül Ciğer; Bülent Kınay; Murat Ocak (PLoS ONE, 2025)
This paper investigates the effect of the number of key audit matter disclosures (KAMs) on audit report lag, focusing on Turkey, an emerging country. The main findings indicate that the number of KAMs positively influences audit report lag in Turkey. System GMM results reinforce our primary estimations, supporting the robustness of our findings. Notably, auditing by large audit firms moderates the effect of KAM numbers of on audit report lag. We categorized KAMs into four sub-types and found that only revenue-related KAMs significantly increase audit report lag. Additionally, various corporate governance, audit firm, and individual auditor attributes influence the number of KAMs reported.